Nonlinear dynamic response of a tall building to near-fault pulse-like ground motions - Gunes, Necmettin; Ulucan, Zulfu Cinar (Springer, 2019)
The objective of this study is to determine the effects of near-fault ground motions with large, medium and small pulse periods on a core-wall tall building. Three near-fault and one far-field ground motion sets, each with 11 different records, are rotated to the maximum pseudo-velocity spectrum directions. The mean transition periods of each set are obtained by the smoothed tripartite spectrum, which illustrates that the acceleration-sensitive region extends with increasing pulse duration. A 40-story core-wall building is subjected to 44 different record pairs, and the analysis results show that the ratio of pulse duration to first mode period (T-p/T-1), governs the nonlinear response. It is demonstrated that higher mode effects increase while the first mode sensitive region moves away from the second mode sensitive region. The distribution profiles of the story drift, tension strain, and beam rotation demands along the height of the building are substantially different depending on the T-p/T-1 ratio. In the large and medium pulses records, the core-wall reaches the flexural yielding capacity above the podium level, and this phenomenon increases the story drift ratio and flexural beam rotation demands depending on the displacement demands at the end of the acceleration-sensitive region. On the contrary, near-fault with small pulses and far-field ground motions induce yielding of core-wall at upper stories due to higher mode effects. Thus, post-yield story shear force distributions significantly change compared to the large and medium pulses ground motions.
Keywords: Near-fault ground motions; Pulse period; Nonlinear dynamic analysis; Higher mode effects; Tall buildings